EKSISTENSI PONDOK PESANTREN DI TENGAH ARUS MODERNISASI (STUDI PADA PONDOK PESANTREN MUQIMUS SUNNAH DI KECAMATAN ILIR BARAT II KOTA PALEMBANG) - Defri Okta Diansah; Syarifuddin Syarifuddin; Alian Alian (Tarbiyatuna Kajian Pendidikan Islam, 2022)
This study was made to discuss the existence of Islamic boarding schools in the midst of modernization (Studies at Muqimus Sunnah Islamic Boarding School in Ilir Barat II District, Palembang City). Islamic boarding schools are the oldest Islamic educational institutions in the archipelago. Along with the occurrence of social changes and modernization in all fields, one of which is modernization in the field of education, of course it affects the existence of traditional Islamic educational institutions such as Islamic boarding schools. With this condition, it directly or indirectly affects the existence of Islamic Boarding Schools. This study aims to find out such conditions in depth about how the existence of Islamic boarding schools exists in the midst of modernization, using the method used is qualitative research with descriptive research. The results of the study show that the contribution that has been made to the community has made the existence of Islamic boarding schools able to survive in the midst of modernization as the community is interested in sending their children to Muqimus Sunnah Islamic Boarding School.